2020
DOI: 10.1038/s41467-020-15003-7
|View full text |Cite
|
Sign up to set email alerts
|

The X-linked trichothiodystrophy-causing gene RNF113A links the spliceosome to cell survival upon DNA damage

Abstract: Prolonged cell survival occurs through the expression of specific protein isoforms generated by alternate splicing of mRNA precursors in cancer cells. How alternate splicing regulates tumor development and resistance to targeted therapies in cancer remain poorly understood. Here we show that RNF113A, whose loss-of-function causes the X-linked trichothiodystrophy, is overexpressed in lung cancer and protects from Cisplatin-dependent cell death. RNF113A is a RNA-binding protein which regulates the splicing of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…The loss of E3 ubiquitin–protein ligase ring finger protein 113A (RNF113A) triggers DNA damage-related ferroptosis. 125 Lon peptidase 1, mitochondrial (LONP1) is an essential stress response protease that mediates mitochondrial proteostasis. LONP1-mediated degradation of transcription factor A, mitochondrial (TFAM) induces mitochondrial DNA damage, which causes ferroptosis in pancreatic cancer cells through the activation of stimulator of interferon response CGAMP interactor 1 (STING1/TMEM173)-dependent autophagy.…”
Section: Degradation Systemsmentioning
confidence: 99%
“…The loss of E3 ubiquitin–protein ligase ring finger protein 113A (RNF113A) triggers DNA damage-related ferroptosis. 125 Lon peptidase 1, mitochondrial (LONP1) is an essential stress response protease that mediates mitochondrial proteostasis. LONP1-mediated degradation of transcription factor A, mitochondrial (TFAM) induces mitochondrial DNA damage, which causes ferroptosis in pancreatic cancer cells through the activation of stimulator of interferon response CGAMP interactor 1 (STING1/TMEM173)-dependent autophagy.…”
Section: Degradation Systemsmentioning
confidence: 99%
“…Very recently, another study has shown that RNF113A is recruited to sites of DNA damage and found that RNF113A is important for regulating DNA repair factor recruitment to chromatin [ 115 ]. This work also showed that RNF113A co-localized with phosphorylated DNA-PK cs in cisplatin-treated cells [ 115 ], however as our study did not look at interaction in the context of double-stranded breaks, it is presently unclear why this protein may be found in proximity to Ku70. We have previously found that Ku appears to be in close proximity to many DNA repair factors and sensors, even in the absence of DNA damage [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since we previously found that recombinant RNF113A showed no E3 activity (Brickner et al, 2017), we used RNF113A complex purified from HeLa-S cell nuclear extracts, as above, and tested the ability of methylated RNAs to induce its E3 ligase activity. Due to its association with the spliceosome (Hegele et al, 2012;Shostak et al, 2020), we first used in vitro transcribed bglobin pre-mRNA (Movassat et al, 2014) as a potential substrate for inducing RNF113A E3 activity. While the unmodified RNA had a mild stimulatory effect on the E3 activity of RNF113A, we saw a marked increase in the E3 activity when the same RNA was premethylated using dimethyl sulphate (DMS; Figure 5A).…”
Section: In Vitro Activation Of Rnf113a E3 Ligase By Methylated Rnamentioning
confidence: 99%